Special Curves According to Bishop Frame in Minkowski 3-Space - Isah, Muhammad Abubakar; Kulahci, Mihriban Alyamac (Walter de Gruyter Gmbh, 2020)
Pseudo null curves were studied by some geometers in both Euclidean and Minkowski spaces, but some special characters of the curve are not considered. In this paper, we study weak AW(k) - type and AW(k) - type pseudo null curve in Minkowski 3-space E-1(3). We define helix and slant helix according to Bishop frame in E-1(3). Furthermore, the necessary and sufficient conditions for the slant helix and helix in Minkowski 3-space are obtained.
Keywords: Bishop frame; Pseudo null curve; slant helices